Implementation of IPv6 services over a GMPLS-based IP - Tatipamula, Mallik (IEEE Communications magazine)
In recent days, there has been considerable interest in deploying IPv6-based services. Trial and commercial IPv6 services offering has already begun, especially in Japan, Korea, China, and other parts of the world. At the same time, many service providers have embraced MPLS as the enabler for the required multiservice capabilities of their next-generation packet networks. Also, the widespread deployment of DWDM-based optical transport systems in the core network to satisfy the tremendous need and increase in capacity demand has led network planners to reconsider traditional approaches to provisioning and network restoration, and plan integration of the optical layer into the MPLS infrastructure according to the emerging GMPLS technology. The purpose of this article is to discuss next-generation network architecture evolution and present a detailed architecture for transport of emerging IPv6 services and applications over next-generation GMPLS multiservice backbone networks. This article also presents an implementation and demonstration of this technique for IPv6 transport over a GMPLS backbone network as well as interoperability verification of IPv6 and GMPLS using a GMPLS network testbed.